FACTORS ASSOCIATED WITH EARLY OUTCOMES AFTER PRIMARY PERCUTANEOUS CORONARY INTERVENTION IN PATIENTS AGED ≥75 YEARS WITH ST-ELEVATION MYOCARDIAL INFARCTION (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate several factors affecting the outcome of percutaneous coronary intervention (PCI) within 30 days in patients aged ≥75 years with ST-elevation myocardial infarction (STEMI).Subjects and Methods: A cross-sectional descriptive study was conducted on 104 patients aged ≥75 years who were diagnosed with ST-elevation myocardial infarction (STEMI) and indicated for primary percutaneous coronary intervention (PCI) at the Vietnam National Heart Institute – Bach Mai Hospital, Hanoi Heart Hospital, and Huu Nghi Hospital from 2018 to 2021.Results: The incidence of major adverse cardiovascular events (MACE) was 10.6%. Age ≥85 years (OR = 5.37; p = 0.006), Killip class III and IV (OR = 4.74; p = 0.028), TIMI score >6 (OR = 9.79; p = 0.011), CK-MB >39 U/L (OR = 4.11; p = 0.032), elevated Troponin T >4084.2 ng/L (OR = 6.19; p = 0.008), and ST elevation ≥4.0 mm (OR = 6.24; p = 0.003) were associated with an increased risk of MACE within 30 days after primary PCI in elderly patients.Conclusion: Factors associated with adverse outcomes after primary PCI in patients aged ≥75 years with STEMI within 30 days included advanced age, high Killip class, TIMI score >6, elevated CK-MB, Troponin T levels, and ST elevation ≥4.0 mm.